Mouse models of preeclampsia with preexisting comorbidities - Waker, Christopher A.; Hwang, Amy E.; Bowman-Gibson, Scout; Chandiramani, Chandni H.; Linkous, Bryce; Stone, Madison L.; Keoni, Chanel I.; Kaufman, Melissa R.; Brown, Thomas L. (Frontiers in Physiology, 2023)
Preeclampsia is a pregnancy-specific condition and a leading cause of maternal and fetal morbidity and mortality. It is thought to occur due to abnormal placental development or dysfunction, because the only known cure is delivery of the placenta. Several clinical risk factors are associated with an increased incidence of preeclampsia including chronic hypertension, diabetes, autoimmune conditions, kidney disease, and obesity. How these comorbidities intersect with preeclamptic etiology, however, is not well understood. This may be due to the limited number of animal models as well as the paucity of studies investigating the impact of these comorbidities. This review examines the current mouse models of chronic hypertension, pregestational diabetes, and obesity that also develop preeclampsia-like features and discusses how closely these models recapitulate the human condition. Finally, we propose an avenue to expand the development of mouse models of preeclampsia superimposed on chronic comorbidities to provide a strong foundation needed for preclinical testing.